A dual-layered artificial solid electrolyte interphase formed by controlled electrochemical reduction of LiTFSI/DME-LiNO3 for dendrite-free lithium metal anode. (20th May 2019) - Zhang, Chunqing; Lan, Qing; Liu, Yutao; Wu, Jiliang; Shao, Huixia; Zhan, Hui; Yang, Yifu
Abstract: Dendrite growth and low coulombic efficiency (CE) are the key issues to hinder the lithium (Li) metal anode in practical battery application. Naturally formed fragile and unstable solid electrolyte interphase (SEI) film between Li anode and electrolyte is one of the main reasons for them. Here we create a dual-layered artificial SEI (ASEI) film by controlled electrochemical method, which can simultaneously suppress dendrite formation and improve electrochemical performance of Li metal anode. The ASEI film with an average thickness of 40 nm shows a dual-layered structure with organic species (−(CH2 CH2 O)n − and lithium alkylcarbonate) in the outer layer and abundant inorganic species (LiF, Li2 O, Li3 N and Li2 S) in the inner layer, providing enough flexibility, high mechanical modulus, high kinetic and thermodynamic stability. The ASEI film demonstrates extremely superior Li + ion conductivity and low interface impedance, enabling a compact and dendrite-free Li deposition during cycling, and remarkably improving the CE to an average value of 97.5% for over 350 cycles. The superior electrochemical performance of lithium−sulfur (Li−S) full cells with the protection of ASEI film on Li anode further proves that the ASEI film has optimistic potential in Li metal batteries. This work provides a simple and feasible strategy for preparing ASEI film for dendrite-free Li metal anode, which has great prospects in high specific energy Li metal batteries. Graphical abstract: Image 1 Highlights: Creation of ASEI by controlled electrochemical reduction of LiTFSI/DME-LiNO3 . Dual-layer structure of ASEI provides excellent performance of Li metal anode. Protection mechanism of the ASEI for Li metal anode has been provided.